Dynactin Subunit p150(Glued) Is a Neuron-Specific Anti-Catastrophe Factor - Lazarus, Jacob E. (Public Library of Science, 2013)
Regulation of microtubule dynamics in neurons is critical, as defects in the microtubule-based transport of axonal organelles lead to neurodegenerative disease. The microtubule motor cytoplasmic dynein and its partner complex dynactin drive retrograde transport from the distal axon. We have recently shown that the p150(Glued) subunit of dynactin promotes the initiation of dynein-driven cargo motility from the microtubule plus-end. Because plus end-localized microtubule-associated proteins like p150(Glued) may also modulate the dynamics of microtubules, we hypothesized that p150(Glued) might promote cargo initiation by stabilizing the microtubule track. Here, we demonstrate in vitro using assembly assays and TIRF microscopy, and in primary neurons using live-cell imaging, that p150(Glued) is a potent anti-catastrophe factor for microtubules. p150(Glued) alters microtubule dynamics by binding both to microtubules and to tubulin dimers; both the N-terminal CAP-Gly and basic domains of p150(Glued) are required in tandem for this activity. p150(Glued) is alternatively spliced in vivo, with the full-length isoform including these two domains expressed primarily in neurons. Accordingly, we find that RNAi of p150(Glued) in nonpolarized cells does not alter microtubule dynamics, while depletion of p150(Glued) in neurons leads to a dramatic increase in microtubule catastrophe. Strikingly, a mutation in p150(Glued) causal for the lethal neurodegenerative disorder Perry syndrome abrogates this anti-catastrophe activity. Thus, we find that dynactin has multiple functions in neurons, both activating dynein-mediated retrograde axonal transport and enhancing microtubule stability through a novel anti-catastrophe mechanism regulated by tissue-specific isoform expression; disruption of either or both of these functions may contribute to neurodegenerative disease.